THE IMPACT OF PLASTIC PRICE INCREASES ON THE PURCHASING POWER OF THE COMMUNITY IN BATAM CITY - Oktapia Asif Rahmayanti; Raden Imam Al Hafis (Indonesian Journal of Social Sciences, Policy and Politics, 2026)
This study aims to describe the magnitude of plastic price increases in Batam City and to examine their impact on community purchasing power. From late February to early March 2026, plastic product prices in Batam experienced a significant surge driven by geopolitical instability in the Middle East, which disrupted global energy distribution routes, particularly through the Strait of Hormuz, thereby raising the cost of petrochemical-based raw materials such as naphtha. This study employed a qualitative descriptive approach with data collection conducted through semi-structured field interviews, literature review, and documentation from credible journalistic and academic sources. Three informants were selected through purposive sampling: a plastic packaging distributor, a small and medium-sized enterprise (SME) representative, and a household consumer in Batam City. Data validation was performed through source triangulation by cross-referencing interview findings with media reports and academic literature. The findings indicate that plastic price increases in Batam City ranged from 50 to 100 percent depending on product type, consistent with patterns identified in national studies. The increases produced layered cost-push inflation effects across the supply chain: distributors faced sudden and unannounced price surges from suppliers; SME representative absorbed rising packaging costs to maintain customer retention; and household consumers reduced expenditure and shifted toward reusable alternatives. Cascading effects on the prices of related commodities, including cooking oil, were also observed. This study recommends short-term social protection interventions, fiscal incentives for eco-friendly packaging transitions, and structural strengthening of the national petrochemical industry to reduce Indonesia's dependence on imported plastic raw materials.